2019
DOI: 10.25186/cs.v14i1.1542
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Techniques for Mitigating the Effects of Water Restriction on Coffee Crops

Abstract: Water restriction significantly affects coffee (<em>Coffea arabica</em> L.) production. The study of a few agronomic techniques that optimizes water use can generate technologies for mitigating the effects of climatic variations on coffee crops. The aim of this study was to indicate agronomic techniques that mitigate the effects of water restriction on coffee crops. For this end, we analyzed the morphophysiological changes in coffee plants cultivated in a greenhouse with different types of fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The use of water-retaining polymers reportedly enhanced the performance of plants showing more favorable anatomical characteristics to make physiological processes more efficient regardless of water availability (Castanheira et al, 2019). Consistently, Souza et al (2016), observed greater plant growth upon soil treatment with water-retaining polymers than in their absence.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The use of water-retaining polymers reportedly enhanced the performance of plants showing more favorable anatomical characteristics to make physiological processes more efficient regardless of water availability (Castanheira et al, 2019). Consistently, Souza et al (2016), observed greater plant growth upon soil treatment with water-retaining polymers than in their absence.…”
Section: Introductionmentioning
confidence: 75%
“…The correct use of irrigation or other technologies to optimize water use (such as the use of water-retaining polymers) increases coffee plant growth while minimizing or even eliminating harmful effects of water deficit (Assis et al, 2014;Carvalho et al, 2006;Castanheira et al, 2019). Oliveira et al (2014) found that the use of the waterretaining polymer technology favored both an increase in palisade parenchyma thickness and greater chloroplast abundance, thereby contributing to the photosynthetic process.…”
Section: Discussionmentioning
confidence: 99%
“…A adoção de práticas vegetativas como a manutenção de vegetação nos carreadores do cafeeiro favorece a retenção de umidade do solo (CASTANHEIRA et al, 2019).…”
Section: Resultsunclassified
“…The adaptation of plants to a given environment can be better understood by knowing the physiological mechanisms involved in the regulation of their metabolism, such as photosynthetic rate, stomatal transpiration and water use efficiency, which can indicate the level of adaptation to a condition of stress or even differences between genotypes under an optimal cultivation condition (Verissimo et al, 2010). Stomatal conductance can be affected by water stress and temperature (Iseki;Olaleye, 2020;Castanheira et al, 2019). Although the seedlings of 'MGS Paraíso 2' had lower stomatal conductance values, this cultivar had good performance for several growth characteristics (Table 1), dry matter weight (Table 2), root system (Table 3) and chlorophylls (Table 4), showing that the lowest SC value does not necessarily imply less development.…”
Section: Ciência E Agrotecnologia 45:e017821 2021mentioning
confidence: 96%
“…According to Trazzi et al (2013), seedling quality is directly linked to yield and quality of the final product. In the context of coffee seedling production, in recent years, research has been conducted using alternative substrates (Vallone et al, 2010;Meneghelli et al, 2017), adaptation of seedlings in shading systems and full sun (Castanheira et al, 2019), among others.…”
Section: Introductionmentioning
confidence: 99%